GhCLCg-1, a Vacuolar Chloride Channel, Contributes to Salt Tolerance by Regulating Ion Accumulation in Upland Cotton - Liu, Wei; Feng, Junping; Ma, Wenyu; Zhou, Yang; Ma, Zongbin (Frontiers in Plant Science, 2021)
Soil and freshwater salinization is increasingly becoming a problem worldwide and has adversely affected plant growth. However, most of the related studies have focused on sodium ion (Na+) stress, with relatively little research on chloride ion (Cl−) stress. Here, we found that upland cotton (Gossypium hirsutum) plants accumulated Cl− and exhibited strong growth inhibition under NaCl or KCl treatment. Then, a chloride channel gene (GhCLCg-1) was cloned from upland cotton. Phylogenetic and sequence analyses indicated that GhCLCg-1 was highly homologous to AtCLCg and also have conserved voltage_CLC and CBS domains. The subcellular localization assay showed that GhCLCg-1 was localized on the vacuolar membrane. Gene expression analyses revealed that the expression of GhCLCg-1 increased rapidly in cotton in response to chloride stress (NaCl or KCl), and the transcript levels increased as the chloride stress intensified. The overexpression of GhCLCg-1 in Arabidopsis thaliana changed the uptake of ions with a decrease of the Na+/K+ ratios in the roots, stems, and leaves, and enhanced salt tolerance. In contrast, silencing GhCLCg-1 in cotton plants increased the Cl− contents in the roots, stems, and leaves and the Na+/K+ ratios in the stems and leaves, resulting in compromised salt tolerance. These results provide important insights into the toxicity of chloride to plants and also indicate that GhCLCg-1 can positively regulates salt tolerance by adjusting ion accumulation in upland cotton.